Research on the promotion of digital teaching and learning toward achieving China’s dual-carbon strategy - Xinfa, Tang; Yifei, Sun; Chenhui, Zhang; Lihong, Wu; Yan, Luo (Frontiers in Environmental Science, 2023)
The dual-carbon strategy of China affects all walks of life, all of which will be affected in realizing these goals. The same is true of the education sector, and China has the world’s largest education population. The education sector has a large potential to reduce carbon emissions due to its high carbon consumption. Based on the requirements of carbon emission reduction in education, this paper studied the contribution of digital teaching and learning and the education sector toward reducing carbon emissions and discusses how to promote the mechanism construction of carbon emission reduction in the education sector. The study used a comparative analysis and questionnaire research method to analyze the impact of digital teaching and learning on energy saving and emission reduction in the education sector. Research shows that using the Internet and fully utilizing the advantages of digital teaching and learning could improve the quality of teaching, reduce carbon emissions, and help achieve the goal of dual-carbon.